2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--23060
|View full text |Cite
|
Sign up to set email alerts
|

Student Videos as a Tool for Elementary Teacher Development in Teaching Engineering: What Do Teachers Notice? (Research to Practice)

Abstract: is a PhD student in STEM Education at Tufts University. She received a BS in Civil Engineering from University of Massachusetts Lowell and an MS in Civil Engineering from Tufts University. Her current research involves exploring how elementary students' nascent resources for engineering design emerge during integrated engineering and literacy activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As a growing number of United States elementary schools offer formal engineering learning experiences in response to the Next Generation Science Standards and other calls for increased STEM education (National Academy of Engineering and National Research Council, 2014), teachers often notice that engineering affords an opportunity to work toward important goals they already have for children: to become better decision makers, collaborators, and problem solvers (McCormick, Wendell, & O'Connell, 2014). Published guidelines for quality precollege engineering education (Moore et al, 2014) can help elementary educators choose and implement an effective engineering curriculum, but questions remain about what classroom norms, differentiation strategies, and other tailored scaffolds -beyond curriculum materials -will best help their particular students succeed in the decision-making and collaboration aspects of engineering design.…”
Section: Introductionmentioning
confidence: 99%
“…As a growing number of United States elementary schools offer formal engineering learning experiences in response to the Next Generation Science Standards and other calls for increased STEM education (National Academy of Engineering and National Research Council, 2014), teachers often notice that engineering affords an opportunity to work toward important goals they already have for children: to become better decision makers, collaborators, and problem solvers (McCormick, Wendell, & O'Connell, 2014). Published guidelines for quality precollege engineering education (Moore et al, 2014) can help elementary educators choose and implement an effective engineering curriculum, but questions remain about what classroom norms, differentiation strategies, and other tailored scaffolds -beyond curriculum materials -will best help their particular students succeed in the decision-making and collaboration aspects of engineering design.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from this study describe one group of elementary PSTs' attention, analysis, and response to student thinking with engineering DCIs offering a window into their professional noticing of students' thinking (Sherin, 2001) during their first experience teaching an integrated science/engineering STEM unit. These findings build upon the research on PSTs' preparation for engineering design (Dalvi & Wendell, 2017;McCormick et al, 2014;Wendell, 2014). The analysis of the data suggests a number of factors affecting PSTs' professional noticing of students' engineering thinking and their promotion of the NGSS engineering DCIs that teacher educators can consider when developing their STEM methods courses.…”
Section: Discussionmentioning
confidence: 57%
“…Studies have indicated that elementary teachers tend to be unfamiliar with design, engineering, and technology; hold overly broad views about the work of engineers; and have conceptions that do not necessarily align with the NGSS definitions of engineering disciplinary core ideas and practices (Cunningham, Lachapelle, & Lindgren-Streicher, 2006;Hammack & Ivy, 2017;Hsu, Purzer, & Cardella, 2011). Furthermore, research has indicated that there is variability in elementary teachers' perceptions of how to teach engineering design and how to respond to students' design ideas (Capobianco, Diefes-Dux, & Mena, 2011;McCormick et al, 2014;Wendell, Swenson, & Dalvi, 2016). Teachers may adopt a conventional teacherdirected approach whereby students use a step-by-step linear process to problem-solving and teachers instruct students in science concepts to apply to the engineering problem, and/or teachers may operate from a student-constructivist frame of learning encouraging student sense-making of the design process to figure things out.…”
Section: Engineering Design In Elementary Gradesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on teacher noticing in engineering education is in its early stages relative to mathematics and science education [23][24][25][26][27]. We located five studies about teacher noticing in engineering education.…”
Section: Noticing In Engineering Educationmentioning
confidence: 99%